Visualizing psychiatric formulation. (October 2015) - Alyami, Hussain; Sundram, Frederick; Hill, Andrew G; Alyami, Mohsen; Cheung, Gary
Objective: Despite the importance of psychiatric formulation, it remains one of the most challenging tasks for medical students and trainees. To facilitate teaching and learning this essential skill, we propose a visual metaphor in order to conceptualise psychiatric formulation. Conclusions: It is expected that this paper will assist educators and learners to better conceptualise psychiatric formulation through activating prior knowledge through this visual metaphor. Future educational research will determine the effectiveness of this proposed learning tool.